Parity-Preserving Light-Matter System Mediates Effective Two-Body Interactions - Romero-Huenchunir, G; Allende-Prieto, S (Institute of Physics Publishing, 2017)
We study the equilibrium and non-equilibrium physics of two qubits interacting through an ultrastrong coupled qubit-cavity system. By tuning the qubits energy gap while keeping the ultrastrong coupling system to its ground state, we demonstrate a strong two-qubit interaction as well as an enhanced excitation transfer between the two qubits. Our proposal has twofold implications: a means to attain multipurpose parity-protected quantum information tasks in superconducting circuits and a building block for ultrastrong coupled cavity-enhanced exciton transport in disordered media. © 2017 IOP Publishing Ltd.